Testing of wells with horizontal completion in the conditions of terrigenous deposits of the Vietnamese shelf - Agishev Ernest (E3S Web of Conferences)
The article presents a comprehensive approach to the design and results of drilling the first horizontal well in terrigenous deposits of one of the fields offshore Vietnam. A set of works to reduce risks in terms of wellbore wall stability, drilling and optimization of the horizontal section completion scheme has been developed and implemented. Using a geomechanical model based on core study data, the conditions for wellbore wall stability were determined when drilling at high zenith angles and in tectonic fault zones. The use of geosteering technology and optimization of the completion scheme made it possible to exceed the planned well performance indicators. The obtained results prove the high efficiency of the horizontal completion method in the development of single-layer sections of the Vietnamese shelf fields.